“A Study On Financial Performance Analysis Of Spinning Mills Of Coimbatore City” (International Journal of Scientific Research and Management (IJSRM), 2015)
Financial Analysis is the process of identifying the financial strengths and weaknesses of the firm by properly establishing relationships between the items of the Balance Sheet and the Profit and Loss Account. The project work is an outcome of “A study on financial performance analysis of spinning mills of Coimbatore city”. The study was carried out for the period of five years (2010-14) to analyze the financial performance of the company and the 5 companies are Lakshmi Mills, Bannari Amman Spinning Mill, Sri Ramakrishna Spinning Mill, Kpr Spinning Mill and Super Spinning Mill are taken for study. The research design of the study is descriptive research design and secondary data was collected from the published websites of organization for the research. The tools used for analysis is comparative ratio analysis of the balance sheet. Suitable ratios were framed and calculated to know the financial performance of the company. The findings from the analysis were discussed in detail and suggestions for corrective actions like maintain good solvency in order to meet short term and long term obligations were given wherever applicable.